Blizzard City: Built Environment and Civilization in Antarctica, 1911-1961 - Moffat-Wood, Alex (11690293) (2012)
This thesis investigates four Antarctic built environments between 1911 and 1961: Robert Falcon Scott’s 1910-1912 Terra Nova expedition base at Cape Evans, Ross Island; Sir Douglas Mawson’s 1911-1914 Australasian Antarctic Expedition base at Commonwealth Bay; Australia’s Mawson Station in MacRobertson Land, founded in 1954; and New Zealand’s Scott Base, also on Ross Island, founded in 1957. Examining unpublished and published diaries of expeditioners, government files and newspaper reports, this thesis demonstrates that, to the expeditioners who built and occupied them, these places created protective bastions of civilization in an extreme environment. It investigates what residents and architects (figurative and literal) thought and felt about these blizzard cities, their meaning and significance. In doing so, this study reinforces, extends, and at times challenges broader conceptions of built environment, nature, civilization, Antarctica, and their thicket of interrelationships. The first two chapters – one focused on the Heroic Era and the second on the post-WWII bases – argue that Antarctic built environments were embattled, modern sanctuaries. The extreme environment of Antarctica also demonstrated to expeditioners that built environment had plasticity, which challenged the expeditioners’ expectation of built environment being stable, durable, and impermeable. Chapter three argues that Antarctic built environment allowed expeditioners to create civilization in the wilderness, in a variety of ways. Through examining facets of occupation such as etiquette and international cooperation, the chapter argues that civilization took many forms, not all of them positive from the expeditioners’ point-of-view.